The first hijrah: Remembering the migration of the followers of the prophet Muhammad to Ethiopia as an effort to reduce intolerance in Indonesia - William Wahyu Sembiring (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Due to increased extremism and conservatism, Christian-Islam ties in Indonesia have deteriorated in recent years. The real impact of these events is intolerance in numerous facets of Indonesian life. This article aims to analyze the migration of followers of the Prophet Muhammad to Ethiopia as a joint event between the two major religious communities in the world, namely Islam and Christianity. This event contains meaning and value that show the excellent relations between the two Abrahamic religions since Islam first arrived. This study uses a qualitative-historical method by looking at and comparing several written sources, such as Binsar J. Pakpahan’s theory about the theology of remembrance, as a reference in explaining the historical situation that occurred. The results of this paper show that remembering past events can be used to reduce extremism, conservatism, and intolerance.